Robotic-assisted free flap harvesting for diverse soft tissue reconstruction: a PRISMA scoping review of clinical outcomes over the last decade - Fizzah Arif; Owais Ahmed; Mohammad Fazlur Rahman; Sobia Yasmeen; Safdar Ali Shaikh (Journal of the Pakistan Medical Association, 2024)
Introduction: The aim of our study was to assess the advantages and limitations of robotic technology in diverse reconstructive procedures. Methods: A scoping review was conducted in Oct’23, on published studies from 2013 to 2023, focussing onIntroduction: The aim of our study was to assess the advantages and limitations of robotic technology in diverse reconstructive procedures. Methods: A scoping review was conducted in Oct’23, on published studies from 2013 to 2023, focussing on robotic-assisted free flap harvesting. Three databases Ovid-MEDLINE, Scopus, and PubMed were searched. Original research studies reporting robotic-assisted free flap harvest were included. Studies on lesion excision, microvascular anastomosis, local flap harvest, roboticassisted flap inset, review articles, abstract-only studies, non-English documents, and animal studies were excluded from this review. Results: Sixteen studies met the inclusion criteria out of a total of 318, searched initially. These studies included a total of 128 patients, who underwent robotic-assisted free flap harvest for the reconstruction of various defects, with 140 free flaps harvested. The most common flaps harvested by robotic technique were deep inferior epigastric artery perforator (DIEP) flap 120 (85.7%), radial forearm free (RFF) flap 11 (7.9%), latissimus dorsii flap 4 (2.9%), rectus abdominus flap 4 (2.9%), and omental flap 1 (0.7%). Breast reconstruction was the major procedure done i.e. 120 (85.7%) followed by head and neck 11 (7.9%) and limb defects 9 (6.4%) reconstruction procedures. The reported clinical outcomes were acceptable in all the studies with a 99% flap success rate and minimal complications. Variability in operating time was observed depending upon surgical steps undertaken with robotic systems. Conclusion: This scoping review highlights the role of robotic-assisted free flap harvesting in plastic surgery and its potential benefits on clinical outcomes, due to its high precision and minimal invasiveness. However, challenges like cost effectiveness, resource distribution and learning curve are there. Keywords: Tissue Flaps, Epigastric Arteries, Rectus Abdominis, Robotic Surgery, Plastic Mammaplasty, Anastomosis, Surgical, Bibliometrics, Reconstructive Surgery.